A utilização de tecnologias de informação e comunicação em espaços coletivos: considerações sobre a interação dos usuários a partir do estudo do conjunto IAPI - Karina Luna Maciel Cananea (2011)
This paper provides pointers to the use of information and communication technologies (ICT) in the context of the collective spaces of the housing estate Instituto de Aposentadoria de Pensão dos Industriários (IAPI), focusing on technological experiences that include interactive situations between people, technologies and environments. Although the practice of architects and urban planners is often marked by the concentration of decisions on processes of production of space, the rhythm that the appropriation of space aquires to accommodate unforeseen uses and configurations outlines the important role of theuser that exceeds the limits of architectural design. On this issue a few ways to insert the user in the process of building, construction, and occupation, have been studied since the middle of the last century. In order to encourage their engagement in all stages of production of space, the new ICTs have shown themselves as allies towards expanding not only the ability to interact, but also the autonomy of users. In this context the present study investigates approaches that bring architecture and technology closer together, as well as different levels of interactivity resulting from this intersection. The housing chosen is studied having as its source of analysis some insights from the author, home owners and design projects proposed by students in two courses at the School of Architecture of UFMG. Through these it investigates the students' approach to deal with conflicts in the common areas and tomediate them with the use of IT or ICT, as well as other types of approaches to deal with a less imposing design strategy. The findings show that everyday spatial arrangements, with spontaneous rhythms of negotiations, bring a latent sense of autonomy, interaction and continuity, demonstrating the active role of users in the continuous process of production of space, dealing with the spatial conflicts experienced. Another finding is that ICT can mediate a new design process thatsurpasses the passive participation of users presenting them with the possibility of autonomy in the production of space.